Dosimetric characterisation of silica fibre thermoluminescent sensors for medical and non medical applications / Farhad Moradi - Farhad , Moradi (2018)
Silica based optical fibres has been attracting researchers since 1980’s due to various phenomenal observations via the exposure of ionizing radiation. Studies of such phenomena gradually eventuated the potentiality of silica fibres as radiation dosimeters. Focus was made mainly on thermoluminescence (TL) properties with various competitive advantages such as proper spatial resolution, non-hygroscopic nature, cost effectiveness, chemically inert and wide range dose response linearity etc. Available literatures concentrate on the increasing sensitivity of different composition silica fibres, some of their dosimetric characteristics and potential applications. However, there is a significant gap between the published works and practical needs before routine usage of such thermoluminescent dosimeters (TLDs). This study concentrates on properties of Ge-doped silica fibre TLDs, with the first and second phases of the study on characterisation of fibres for general and specific applications respectively. The applications included in-vivo dosimetry in intraoperative radiotherapy using low kV photon field, gamma irradiator dose mapping and high dose dosimetry. To maintain sensitivity and reproducibility of the dosimeter, stabilization process should be optimized. This was done as part of this study. The effect of accumulated dose on TL response and the role of heating on the sensitivity of fibres were investigated, and an optimized preparation procedure was obtained. It was shown that TL response would not be reproducible without applying a pre-dose and sufficiently high annealing temperature. Dependence of the fibre TL response on different beam parameters including beam angulation, beam energy and dose rate was also studied in parts of characterisation. Energy dependence is expected from SiO2 due to its high effective atomic number. It was proven that energy dependence correction factor for Ø=125 μm Ge-doped fibre with small sensitive part (8.5 μm core) at each keV energy can be approximated well by the ratio of mass energy absorption coefficient of the sensitive part of the fibre to that of medium. A considerable angular dependence was also observed from studied fibre TLD in free-in-air irradiations. This was decreased significantly in presence of phantom, where scattered radiation was involved. Respective coefficients at each situation were obtained. The results, in general, remark the importance of positioning and consideration of the angular dependence. Study was extended to introduce new applications benefiting small size, wide dose/response range and waterproof of silica fibres. Dosimetry for the INTRABEAM system, an electronic brachytherapy source, necessitated to characterize the fibres at different depth in water where dose rate and beam quality were simultaneously changed. In addition to experimental approach to achieve better insight into phenomenon, Monte Carlo simulations were also performed. Both the experimental and simulation approaches resulted in determination of calibration coefficients needed for patient dose assessment. In the last part, various silica fibres were tested in terms of their performance under high dose irradiation. Most fibre types showed saturation in doses below 50 kGy, with only borosilicate fibre showing linear dose response of up to 100 kGy. The results of this study generally help to promote the use of silica based fibres as practical TL dosimeters offering sufficient precision.